2022
DOI: 10.3389/fimmu.2022.878832
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization With a c-di-GMP-Adjuvanted Acellular Pertussis Vaccine Provides Superior Immunity Against Bordetella pertussis in a Mouse Model

Abstract: Pertussis, caused by the gram-negative bacterium Bordetella pertussis, is a highly contagious respiratory disease. Intranasal vaccination is an ideal strategy to prevent pertussis, as the nasal mucosa represents the first-line barrier to B. pertussis infection. The current intramuscular acellular pertussis (aP) vaccines elicit strong antibody and Th2-biased responses but not necessary cellular and mucosal immunity. Here, we formulated two cyclic dinucleotide (CDN)-adjuvanted aP subunit vaccines, a mammalian 2’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Serological responses to Bp are used to determine vaccine efficacy and protection in humans (33)and animals (13, 34)and are quantified in nasal secretions or nasal lavage. We found that antibodies in the NL were at the limit of detection, with antibodies in the NT significantly (∼1-2 log) increased in wPV immunized mice.…”
Section: Discussionmentioning
confidence: 99%
“…Serological responses to Bp are used to determine vaccine efficacy and protection in humans (33)and animals (13, 34)and are quantified in nasal secretions or nasal lavage. We found that antibodies in the NL were at the limit of detection, with antibodies in the NT significantly (∼1-2 log) increased in wPV immunized mice.…”
Section: Discussionmentioning
confidence: 99%
“…The flow cytometry procedure was performed according to a previous protocol with minor modifications ( Jiang et al, 2022a ). Procedure details are also provided in the Supplementary material 2.5 .…”
Section: Methodsmentioning
confidence: 99%
“…Oral mRNA vaccines are also being developed [90]. Several intranasal vaccines that combine protein subunits and adjuvants are being designed and tested against pertussis, tuberculosis, and SARS-CoV-2 [91][92][93][94][95][96]. Outer membrane vesicles, which have previously been used in parenteral meningitis B vaccines, are now being used for intranasal pertussis and SARS-CoV-2 vaccines [97][98][99].…”
Section: Importance Of Mucosal Vaccines and Their Developmentmentioning
confidence: 99%